2004
DOI: 10.1136/bmj.38023.700775.ae
|View full text |Cite
|
Sign up to set email alerts
|

Effects of training on quality of peer review: randomised controlled trial

Abstract: Objective To determine the effects of training on the quality of peer review. Design Single blind randomised controlled trial with two intervention groups receiving different types of training plus a control group. Setting and participants Reviewers at a general medical journal. Interventions Attendance at a training workshop or reception of a self taught training package focusing on what editors want from reviewers and how to critically appraise randomised controlled trials. Main outcome measures Quality of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
196
1
9

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 221 publications
(208 citation statements)
references
References 12 publications
2
196
1
9
Order By: Relevance
“…The objective of this paper is to report the frequency with which the nine major and five minor errors were detected and the impact that training had on each of the 14 errors studied. As the methods of the trial and primary results have previously been reported, 10 they are described only briefly in this paper. In this paper the data from the RCT is used as observational data.…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The objective of this paper is to report the frequency with which the nine major and five minor errors were detected and the impact that training had on each of the 14 errors studied. As the methods of the trial and primary results have previously been reported, 10 they are described only briefly in this paper. In this paper the data from the RCT is used as observational data.…”
Section: Researchmentioning
confidence: 99%
“…9 We conducted a single blind randomized controlled trial (RCT) on the effect of training on the performance of peer reviewers of a general medical journal, the BMJ. 10 Reviewers were randomized to one of three groups (control, face-to face training and self-taught) and invited to review three manuscripts during the study period. The training package focused on what editors want from reviewers and how to critically appraise RCTs.…”
Section: Researchmentioning
confidence: 99%
“…Issues resulting from peer review failure range from simple gate-keeping errors, based on differences in opinion of the perceived impact of research, to failing to detect fraudulent or incorrect work, which then enters the scientific record ( Baxt et al , 1998; Gøtzsche, 1989; Haug, 2015; Moore et al , 2017; Pocock et al , 1987; Schroter et al , 2004; Smith, 2006). A final issue regards peer review by and for non-native English speaking authors, which can lead to cases of linguistic inequality and language-oriented research segregation, in a world where research is increasingly becoming more globally competitive ( Salager-Meyer, 2008, Salager-Meyer, 2014).…”
Section: 01 Methodsmentioning
confidence: 99%
“…BMJ actually tested this hypothesis by randomizing reviewers into three groups: one group had no training, one received personal training in addition to a CD-ROM, and the third group received just the CD-ROM. After using a standardized instrument to measure the quality of reviews and counting the number of intentionally placed errors detected by reviewers, the results showed that training made no overall difference [8].…”
Section: Reviewmentioning
confidence: 99%